PENGARUH KETERAMPILAN METAKOGNISI TERHADAP KETERAMPILAN BERKOMUNIKASI DAN KETERAMPILAN BERPIKIR KRITIS - Rina Kurnia Dewi; Undang Rosidin; I Dewa Putu Nyeneng (Jurnal Pembelajaran Fisika, 2013)
Metacognition skills that is belonged to some students at SMPN1 Purbolinggo is weak, so there are students having difficulty to understand the lesson. The objectives of this research to know; The influence metacognition skills toward physics communication skills student of SMP in cooperative learning model TSTS type; The influence metacognition skills toward critical thinking skill students of SMP in cooperative learning model TSTS type. The population of this research are all student at the second semester of VIII class at SMPN 1 Purbolinggo. The sample of this research is VIIID class, it consist of 30 students. Sample class is selected by cluster random sampling. Design of this research is one-shot case study. The result is show that; There is positive influence between metacognition skills toward physics communication skills student of SMP in cooperative learning model TSTS type; There is positive influence between metacognition skills toward critical thinking skill students of SMP in cooperative learning model TSTS type. Keywords: The Influence, Two Stay Two Stray (TSTS), Metacognition Skills, Communication Skills, Critical Thinking Skills.